Critical Analysis of Writing Skills through School Literacy Movement in Grade IV Students of SD Negeri 2 Pamijen - Nur Fitrianingrum; Ine Kusuma Aryani (Proceedings of the 1st International Conference on Social Science (ICSS), 2024)
Literacy is an essential basic ability in the process of education and individual development. In today's information age, literacy skills, especially writing skills, play a crucial role in shaping learners' critical thinking and creativity. Writing is not merely the act of composing words into sentences but a process that involves thinking, understanding, analysis, and structured expression of ideas. Therefore, the development of writing skills is a primary focus of education. The School Literacy Movement (Gerakan Literasi Sekolah, GLS) aims to enhance literacy culture among learners by fostering a supportive learning environment through various reading and writing activities. This study was conducted at SD Negeri 2 Pamijen, Baturraden District, Banyumas Regency, involving 22 grade IV students. The research aimed to critically analyze the impact of GLS on students' writing skills using a qualitative research method. Data were collected through interviews with principals, teachers, and students, observations, and questionnaires. The study found that school literacy activities significantly improved students' writing skills. This improvement was measured by analyzing pre- and post-intervention writing samples, showing a notable enhancement in students' ability to structure their thoughts, use appropriate vocabulary, and engage in critical thinking. The results indicated a significant improvement, with a marked increase in the average writing scores of students post-intervention, demonstrating the effectiveness of GLS in fostering better writing skills.